Social Behavior of Teluk Meranti Community towards Surfing Sports in Kampar River Riau Province - Ahmad Yania, Oktia Woro Kasmini Handayanib,Tjetjep Rohendi Rohidic, Nasuka (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The social behavior of the People of Teluk Meranti regarding surfing sports is a response to the unique natural phenomenon that occurs in kampar river by utilizing bono waves to conduct surfing activities found in kampar river teluk meranti district pelalawan riau province. Bono waves are a natural phenomenon that comes before high tide, bono waves have the potential to be one of the tourist destinations, now bono waves have attracted a lot of local and foreign tourists so it is expected to have a positive impact on the community. Penelitian ini bersifat deskri ptif qualitative dengan menggunakan metode Triangulasi (observasi atau pengamatan, in-depth interviews and documentation) then analyzed using the Nvivo, dil a ks a n a k an in Meranti Bay District pelalawan Riau Province. Informants are the people who are expected to assist the author in uncovering the true reality in a conscientious society. The results of this study explain that the environment in this study is a river that is able to produce waves up to four meters and used for surfing activities. Meanwhile, when viewed from the socio-cultural aspects of the meranti bay community can introduce traditional activities such as the use of waves after the passage of a large wave as many as seven layers of waves for the activity "Bono Riding", and also the people of meranti bay can accept culture that comes from outside even contrary to local customs. In terms of socioeconomic with bono wave tourism and able to bring many tourists indirectly able to support the economy of meranti bay community and also able to bring in Regional Native Income (PAD) Based on the analysis using NVivo which often talks about the environment by 18%, socio-cultural 27% and socioeconomic by 22%.